Esophageal capsule endoscopy is a useful tool in patients with hemophilia - Koulaouzidis, Anastasios; Ang, Yun Lin; Douglas, Sarah; Plevris, John N. (Endoscopy, 2014)
Esophageal capsule endoscopy (ECE) is considered to be an alternative to conventional esophagogastroduodenoscopy (EGD); however, its indications continue to expand. This report presents results from the use of ECE in patients with hemophilia at a tertiary referral academic center over a 7-year period. A total of 16 patients with hemophilia, who were all at risk of new-variant Creutzfeldt-Jakob disease due to previous treatment with UK plasma-derived pooled blood products, underwent a total of 28 ECE examinations. Main outcomes were the diagnostic yield of ECE, requirement for subsequent conventional EGD, and any variceal bleeding episodes during the follow-up period. The overall diagnostic yield was 67.8 % (19 /28 ECEs). Only one patient underwent conventional EGD, for esophageal biopsies. There were no variceal hemorrhage events in any of the patients on variceal screening follow-up. ECE is a useful and acceptable alternative to conventional endoscopy in selected patient groups (i. e. patients with hemophilia). In this group, ECE can eliminate the need for prior administration of clotting factors.